Exergy analysis of solar gas turbine system coupled with Kalina cycle. (2015) - Peng, Shuo; Hong, Hui
This paper provides an exergy analysis of a solar gas turbine system coupled with Kalina cycle with the aim of examining the exergy destruction in key components and seeking the potential to improve the thermodynamic performance of this system. An exergy analysis mode is developed by the concept of energy level. The exergy destruction in key components is illustrated and compared with solar gas turbine system coupled with Rankine cycle. The effect of key parameters namely direct normal illuminance (DNI), concentration ratio, gas turbine inlet temperature, pressure ratio and ammonia concentration on the exergy destruction in key components has been investigated. Results indicate that exergy destruction in solar receiver and in gas turbine increases as DNI and concentration ratio rise. While the exergy destruction in heat exchanger decreases as DNI and concentration ratio rise.